<h2>
Hello!</h2>
The answer is: ![g(x)=-\sqrt[3]{x-1}](https://tex.z-dn.net/?f=g%28x%29%3D-%5Csqrt%5B3%5D%7Bx-1%7D)
<h2>
Why?</h2>
Let's check the roots and the shown point in the graphic (2,-1)
First,
![0=-\sqrt[3]{x-1}\\\\0^{3}=(-\sqrt[3]{x-1})^{3}\\\\0=-(x-1)\\\\x=1](https://tex.z-dn.net/?f=0%3D-%5Csqrt%5B3%5D%7Bx-1%7D%5C%5C%5C%5C0%5E%7B3%7D%3D%28-%5Csqrt%5B3%5D%7Bx-1%7D%29%5E%7B3%7D%5C%5C%5C%5C0%3D-%28x-1%29%5C%5C%5C%5Cx%3D1)
then,
![g(0)=-\sqrt[3]{0-1}\\g(0)=-(-1)\\g(0)=1\\y=1](https://tex.z-dn.net/?f=g%280%29%3D-%5Csqrt%5B3%5D%7B0-1%7D%5C%5Cg%280%29%3D-%28-1%29%5C%5Cg%280%29%3D1%5C%5Cy%3D1)
So, we know that the function intercepts the axis at (1,0) and (0,1), meaning that the function match with the last given option
(
)
Second,
Evaluating the function at (2,-1)
![y=-\sqrt[3]{x-1}\\-1=-\sqrt[3]{2-1}\\-1=-\sqrt[3]{1}\\-1=-(1)\\-1=-1](https://tex.z-dn.net/?f=y%3D-%5Csqrt%5B3%5D%7Bx-1%7D%5C%5C-1%3D-%5Csqrt%5B3%5D%7B2-1%7D%5C%5C-1%3D-%5Csqrt%5B3%5D%7B1%7D%5C%5C-1%3D-%281%29%5C%5C-1%3D-1)
-1=-1
It means that the function passes through the given point.
Hence,
The equation which represents g(x) is ![g(x)=-\sqrt[3]{x-1}](https://tex.z-dn.net/?f=g%28x%29%3D-%5Csqrt%5B3%5D%7Bx-1%7D)
Have a nice day!
Answer:
61
Step-by-step explanation:
1. let the unknown be x
2. using theorem of Pythagoras that states the hypotenuse will be equal to the sum of the other two sides we can determine that 75=14+X
3. this implies that X=75-14
4. therefore X= 61
Answer: 1ST ONE CUZ THE LINE IS AT A CERTAIN ANGLE AT A POINT TO MATCH THE FIRST ANSWER
Step-by-step explanation:
Answer:
= 2.48 × 10¹²
(scientific notation)
= 2.48e12
(scientific e notation)
= 2.48 × 10¹²
(engineering notation)
(trillion; prefix tera- (T))
= 2480000000000
<span>(real number)</span>
From least to Greatest: 8/100, 7/10, 3/5